Fabrication and application of superhydrophobic nonwovens: a review. (December 2022) - Wang, W.; Feng, L.; Song, B.; Wang, L.; Shao, R.; Xia, Y.; Liu, D.; Li, T.; Liu, S.; Wang, L.; Xu, Z.; Deng, H.; et al.
Abstract: The three-dimensional porous structure, excellent mechanical properties, rapid preparation process, and low cost of nonwovens lay a foundation for the fabrication of superhydrophobic nonwovens. Among them, the protogenous three-dimensional structure of nonwovens simplifies the preparation process of superhydrophobic nonwovens to a certain extent. Superhydrophobic nonwoven is one of researches of functional nonwovens due to their high selectivity contraposing to oil and water, water and pollution resistance, self-cleaning performance, and antibacterial property. This review summarizes the effects of fiber fineness and micro-nano hierarchical structure on superhydrophobicity of nonwovens, in particular, overhanging structure and re-entrant structure; discusses the construction methods of superhydrophobic materials, describes in detail the preparation methods of superhydrophobic nonwovens, containing dip-coating method, chemical vapor deposition method, electrospinning, and others; and enumerates their applications in the fields of oil–water separation, self-cleaning, air filter material, and self-healing waterproof material. At the same time, the effects of structure control, interface fabrication, and nonwovens self-structure on superhydrophobicity are prospected. Graphical abstract: Image 1 Highlights: This review summarizes the construction mechanism of superhydrophobic nonwovens. The recent preparation methods and applications of superhydrophobic nonwovens are reviewed. The development of superhydrophobic nonwovens is prospected.